In vitro comparison of the locking loop and continuous cruciate suture patterns - Renberg, W. C.; Radlinsky, M. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
This study was undertaken to test anew suture pattern. Tenorrhaphy wasperformed on 23 pairs of canine deepgluteal tendons. One tendon in eachpair was repaired using a locking loopsuture pattern while the other wasrepaired using a novel continuouscruciate pattern. The tendons weredistracted in a mechanical testing apparatusat a rate of 50 cm/min. Strength atfailure, energy absorbed at failure, andmode of failure were recorded andcompared. The continuous cruciatepattern was stronger at failure andabsorbed greater energy at failure thanthe locking loop pattern. This studyindicated that the continuous cruciatepattern can be used clinically with theknowledge that its strength characteristicsexceed those of the locking looppattern.A new suture pattern was tested in deep gluteal tendons from cadaver dogs. The continuous cruciate suture pattern was found to be significantly stronger than the locking loop pattern in maximum strength and energy absorbed at failure in canine deep gluteal tendons.
Keywords: Tenorrhaphy; suture; tendon